Ectopic intestinal duplication presenting as a congenital gluteal mass - Sahand Bamarni, MD; Salar Berdawd, MBChB; Subhasis Misra, MD, MS, FACS (Elsevier, 2021)
Introduction: Extra-abdominal intestinal duplication is a very condition of unknown etiology. It may be a result of an intestinal duplication with underlying congenital pelvic defect or hernia. The duplicated intestine received its blood supply through an aberrant mesenteric vasculature. Methods: Literature review using PubMed, Medline, and Google Scholar with searching of congenital gluteal mass or gluteal intestinal duplication revealed no previous report of this rare clinicopathologic entity. Result: This report describes a 14 days old full-term female neonate who presents with a left gluteal mass associated with lower limb anomalies. The mass consists of a hernial sac containing a loop of blind-ended small and large bowels associated with a congenital defect in the iliac bone. Conclusion: Gluteal intestinal duplication is seldom considered in the differentials of the gluteal mass. Theoretically, in this particular Case; antenatal herniation of intestinal duplication through the iliac bone defect is a possible etiology.